Penyusunan Kurikulum dalam Pelatihan Vokasi Kejuruan Teknik Listrik Era Revolusi Industri 4.0 di BBPVP Serang - M. Gizwa Afdallah Sachlan; Indra Sudrajat (MASALIQ, 2025)
The Fourth Industrial Revolution presents significant challenges, particularly in the labor sector increasingly dominated by technology and digitalization, thereby necessitating the development of relevant curricula, including in electrical engineering vocational education. This study aims to examine the stages of curriculum development for electrical engineering vocational training in response to the demands of the Fourth Industrial Revolution at the Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Serang. A qualitative method was employed through in-depth interviews with the Sub-Coordinator for Competency Development of Intala and electrical engineering instructors, complemented by document analysis. The findings reveal that curriculum development begins with a Training Need Analysis (TNA), which is subsequently translated into training programs. Additional findings highlight implementation challenges, including limited instructor competence in addressing automation and digitalization, as well as the inadequacy of available equipment. This study concludes that enhancing instructor competence and strengthening collaboration between training institutions and industry are key strategies in developing a vocational curriculum that is adaptive and responsive to the digital era.